An integrated approach to biases in referent-specific judgments. (27th November 2020) - Smith, Andrew R.; Windschitl, Paul D.; Rose, Jason P.
Abstract: Judgments of direct comparisons, probabilities, proportions, and ranks can all be considered referent-specific judgments, for which a good estimate requires a target to be compared against a referent(s). This paper presents a Referent-Specific Judgment Framework (RSJF) to organize and integrate over- and under-estimation biases commonly associated with these judgments. RSJF assumes a dual-process structure in which one key source of bias can arise from spontaneous comparisons whose input—unless offset by a controlled process—can yield an underweighting of evidence about referents. Another key source of bias is the misaggregation of evidence associated with multiple referents. Two studies tested RSJF predictions about similarities and differences in patterns of bias in comparative versus probability judgments. As expected, there was similarity in patterns tied to misweighting and differences in patterns tied to misaggregation. The findings support the utility of RSJF for organizing and advancing the study of referent-specific judgments.